Transcultural religious communication in the age of artificial intelligence: Ethical challenges and opportunities for global harmony - Rustanta, Agustinus (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The development of Artificial Intelligence has fundamentally transformed human communication patterns, including the practice of religious communication that is now taking place in a transcultural digital space. This research aims to critically examine the ethical challenges and opportunities arising from AI's involvement in cross-cultural religious communication. Previous studies have shown that AI is increasingly playing a role in facilitating interfaith dialogue and cross-border spiritual interaction, despite concerns about algorithmic bias, homogenization of spiritual meaning, and commodification of religious values. Methods: This study used a reflective qualitative method with a literature study and critical analysis approach. Data is systematically collected from the latest scientific publications, then analyzed thematically and hermeneutically to capture the complexity of transcultural religious interactions in the digital age. Finding: The results of the study show that AI, on the one hand, opens up opportunities to create spaces for inclusive, participatory, and reflective intercultural dialogue, but on the other hand poses significant ethical risks. These risks include narrowing religious interpretations due to algorithmic bias, loss of richness of local cultural meaning, and manipulation of religious narratives for the benefit of certain markets or ideologies. However, AI has great potential to become a strategic instrument in strengthening global religious harmony if developed and used based on the principles of communication ethics and transcultural awareness. This article recommends implementing strategies such as the development of algorithms that are accountable and adaptive to cultural diversity, strengthening community-based religious digital literacy, and implementing ethical audits of AI-based content. Conclusion: This study concludes that the use of AI in religious communication must be accompanied by close collaboration between technology developers, religious leaders, and academics to ensure that AI becomes a bridge of spiritual solidarity between cultures, not a source of polarization or cultural reduction. Novelty/Originality of this article: The novelty of this article lies in its comprehensive approach, which combines critical reflection on the ethical implications of AI with proposed practical strategies to encourage sustainable transcultural religious communication. This article contributes to enriching the discourse on digital ethics, cross-cultural communication, and the transformation of religiosity in an increasingly digitized global society.